Domain Matching Epitaxial Growth of In2O3 Thin Films on alpha-Al2O3(0001) - Zhang, K; Lazarov, V; Galindo, P; Oropeza, F; Payne, D; Lai, H; Egdell, R (2012)
Oxygen plasma assisted molecular beam epitaxy was used to grow thin films of In 2O 3 on α-Al 2O 3(0001) over a range of substrate temperatures between 300 and 750 °C. The crystal structures and morphologies were examined by X-ray diffraction, transmission electron microscopy, and atomic force microscopy. In all cases, the thermodynamically stable bodycentered cubic phase bcc-In 2O 3 predominates in the films, with an epitaxial relationship In 2O 3(111)||Al 2O 3(0001) and In 2O 3 [11̄10]||Al 2O 3[101̄0] determined by matching between the sublattice oxygen atoms in Al 2O 3(0001) and the In atoms in In 2O 3(111): This involves a 30° rotation of the epilayer unit cell relative to that of the substrate and a 3:2 coincidence structure. A minority fraction of metastable rhombohedral rh-In 2O 3(0001) can be stabilized for substrate temperatures below 550 °C due to the similarity in the bonding symmetries between rh-In 2O 3 and α-Al 2O 3. Despite the large mismatches between In 2O 3 and Al 2O 3 for the two epitaxial systems discussed above (-13.2% for bcc-In 2O 3 and +15.1% for rh-In 2O 3), we show that the epitaxy can be maintained in both cases by matching small but different integral multiples of lattice planes of the In 2O 3 and the substrate at the interface between the two. Thus, the strain is effectively released by dislocations localized at the interface. This so-called domain matching epitaxial growth mode may open up a new route to fabrication of high-quality crystalline thin films of oxides on highly mismatched substrates. © 2011 American Chemical Society.